The development and pilot testing of a behavioral activation-based treatment for depressed mood and multiple health behavior change in patients with recent acute coronary syndrome. - Emily C Gathright; Katherine Diaz Vickery; Woubeshet Ayenew; Matthew C Whited; Melissa Adkins-Hempel; Michelle Chrastek; Jill K Carter; Rochelle K Rosen; Wen-Chih Wu; Andrew M Busch (PLoS ONE)
Background Patients with acute coronary syndrome (ACS) with depressed mood demonstrate poor cardiovascular behavioral risk profiles and elevated risk for recurrent ACS and mortality. Behavioral Activation (BA) offers an intervention framework for an integrated treatment targeting both depression and critical health behaviors post-ACS. Behavioral Activation for Health and Depression (BA-HD) was developed and pilot tested in a multiphase iterative process. Methods First, an initial treatment manual was conceptualized based on the team's prior work, as well as the extant literature. Second, qualitative interviews were conducted with target patients and target providers on the proposed BA-HD treatment rationale, content, and structure. Framework matrix analyses were used to summarize and aggregate responses. Third, an expert panel was convened to elicit additional manual refinements. Finally, patients with post-ACS depression and health behavior non-adherence were recruited to complete an open pilot trial to evaluate acceptability (Client Satisfaction Questionnaire [CSQ], exit interview) and treatment engagement (number of sessions attended; treatment completion was considered completion of 8 out of 10 possible sessions). Results The initial BA-HD treatment manual expanded an existing treatment manual for post-ACS BA-based mood management and smoking cessation to target four health behaviors relevant to post-ACS patients (e.g., smoking cessation, medication adherence, physical activity, and diet). After the initial conceptualization, ten post-ACS patients and eight cardiac rehabilitation professionals completed qualitative interviews. Patients endorsed bi-directional interactions between mood and health behaviors post-ACS. Both patients and providers expressed general support of the proposed treatment rationale and values-guided, collaborative goal-setting approach. Patients, providers, and experts provided feedback that shaped the iterative manual development. After the BA-HD manual was finalized, eight participants were enrolled in a single-arm pilot trial. The mean CSQ score was 30.57 ± 2.23, indicating high satisfaction. Seven out of eight (88%) completed treatment. Pre- to post treatment improvements in depressed mood and health behaviors were promising. Conclusions BA-HD treatment is an acceptable approach to target both mood and health behaviors in post-ACS patients with depression. A future larger, controlled trial is needed to evaluate the efficacy of the BA-HD treatment. Trial registration ClinicalTrials.gov Identifier: NCT04158219.